STAYCATION: TREN PARIWISATA BARU UNTUK MEMAHAMI PERILAKU WISATAWAN (TOURIST BEHAVIOR) MILLENIAL PASCA COVID-19 DI KOTA BANDUNG - Winne Riesky Alifah; Suhirman Suhirman (Warta Pariwisata, 2023)
The purpose of the study was to determine millennial tourist behaviour regarding the decision to doing staycation in hotel during the Covid-19 pandemic. Study Design: This research in the study was descriptive using a quantitative method. Methodology: The study population was consumer or millennial tourist who have stayed in hotels and accommodation around Bandung City. The researchers determined a sample size of 235 respondents. The data collection was performed using a questionnaire consist of multiple choice by selecting a Likert scale. The data processed using SPSS 25. Result: From the profile of 300 respondents of millennial tourist with range 20 – 39 y.o who have stayed in hotel accommodation during the Covid-19 pandemic most of female tourist by 69.4%. Millennial tourist dominated with jobs as a new employees that explain a monthly expenditure budget that can belong to the lower middle class, this group has a good interest in staying at Budget Hotel. Conclusion: From this study we can concluded that the characteristics of millennial tourist choose staycation during Covid-19 pandemic because they need as relaxation. Millennial tourist considered stay at hotel accommodation that have implemented health protocol policies to maintain tourist safety as CHSE Certification.